Relationships among Disability, Quality of Life, and Physical Fitness in Lumbar Spinal Stenosis: An Investigation of Elderly Korean Women - Saejong Park; Ho Sung Han; Gang-Un Kim; Sung Shik Kang; Ho-Joong Kim; Mihyun Lee; Soo Hyun Park; Kyu Hwan Choi; Sung-Ho Kim; Jin S. Yeom (Asian Spine Journal, 2017)
Study DesignA cross-sectional, case-control study.PurposeTo investigate associations between physical fitness measures and disabilities related to back pain and quality of life (QOL) by the presence of symptomatic lumbar spinal stenosis (LSS) in elderly Korean women.Overview of LiteratureLSS leads to decreased functioning and reduced QOL. However, correlations among physical fitness, disability, and QOL have not been investigated in elderly women with LSS.MethodsParticipants included women aged 65 years and older (n=192), divided into a study group (n=38) and a control group (n=154) based on the presence/absence of LSS. All participants underwent physical function and fitness tests. Oswestry disability index (ODI) scores and EuroQol five-dimensional questionnaire (EQ-5D-5L) scores were used to assess disability and health-related QOL.ResultsThe results for the handgrip strength, sit-and-reach, functional reach, and timed up and go (TUG) tests were significantly higher in the control group than the LSS group. ODI scores were significantly higher and EQ-5D-5L scores significantly lower in the LSS group. TUG and functional reach test scores were significantly correlated with ODI scores, and handgrip strength was strongly interrelated with ODI and EQ-5D-5L scores in the LSS group. No other physical fitness measures showed statistically significant relationships with ODI or EQ-5D-5L scores.ConclusionsIn elderly Korean women with LSS, back pain-related disability and QOL are significantly associated with some physical fitness parameters such as handgrip strength. Handgrip strength reflects general muscle strength, which is significantly interrelated with the level of disability and QOL. Our results suggest that enhancing generalized muscle strength helps to reduce disability due to back pain and improve QOL in patients with LSS.